Elevating Argumentation Skills Through Discovery Learning - Swastika, Kayan; Na'im, Mohamad; Safiroh, Ilvatus (Future Science / FSH-PH Publications, 2022)
The 2013 curriculum is oriented toward 21st-century competencies by deploying technology in learning. 21st Century skills hold predominant roles in education. Cognitive skills, critical thinking, creative thinking, metacognitive, perseverance, confidence, solving problem skills, social skills, collaboration, and communication fall under the 21st Century skills. Argumentation skills are important to educators, especially in critical thinking and being able to express opinions or arguments based on data and facts. Learners are required to make decisions on the basis of logical and reasonable information. In improving argumentation skills, a suitable learning model is required, namely Discovery Learning. Discovery learning occurs in problem-solving situations in which learners engage their existing experience and knowledge to discover meaningful new facts, relationships, and truths. As such, Discovery Learning can help learners to improve argumentation skills based on data and facts.